MO028AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE: REGISTRY OF NORTHERN CYPRUS. (29th May 2021) - Bardak, Simge; Oygar, Düriye Deren; Behlul, Ahmet
Abstract: Background and Aims: Autosomal dominant polycystic kidney disease (ADPCK) is the most prevelant inherited kidney disease in adults, and the fourth common cause for renal replacement therapy worldwide and preventive measures should be taken to slow the decline in renal functions. From previous studies we already know that hereditary kidney diseases such as medullary kidney disease and tubular kidney diseases are frequent in Cyprus. In this study, we aim to find out the situation for ADPKC in North Cyprus and declare the overall magnitude of the problem in our region. Method: From January 2004 to January 2021, we collected data from all patients with ADPCK irrespective of whether they were on RRT or not and who were followed in nephrology departments within Northern Cyprus. Clinical and demographic data of all the patients aged above 18 were collected. The affected families and their route of inheritance were determined. Need for renal replacement therapy (RRT) and types of RRT were noted. RRT rate and death rate were calculated. Results: We collected information from a total of 79 patients with the diagnosis of ADPCK; 3 patients were excluded due to lost to follow up. There was no family history in 11% of patients. Inheritence was maternal in 53% and paternal in 42% whereas both maternal and paternal inheritence route were identified in 5%. 68 patients with family history were grouped in 24 families (2.8 patients/ family). The demographic and clinical data can be seen on Table 1 . At some point during follow up 31 patients started with RRT. Mean age for RRT was 55 years (23-81). 5 (16%) patients initiated RRT with peritoneal dialysis, wheras 23 (74%) with hemodialysis, and 3 (10%) had preemptive renal transplantation. At the end of follow up period we found out that 35% (11/31) of patients who had RRT had transplantation, 32% (10/31) experienced peritoneal dialysis whereas 77% (24/31) experienced hemodialysis. 18 out of 76 (24%) patients died during the follow up period. The mean age of death was 71 years (53-81). Conclusion: The prevalance of the disease when living patients were considered was 1.3 cases/10000 inhabitants which is low when compared with other studies. Hence ADPCK was not a common diagnosis in North Cyprus as other hereditary kidney diseases. This may show that some patients are underdiagnosed in the population. The frequency of patients without family history was high and also the number of patients per family was low when compared with other studies; these findings may also indicate an underdiagnosed problem. The patients were diagnosed late at a mean age of 47 Hence we need to perform further studies on ADPCK in our population since identifiying ADPCK patients and their families may help to adress the needs adequately, to plan lifelong supportive measures and to decrease high mortality rate of these patients.